TINGKAT PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG TOKSOPLASMOSIS DI KLINIK SPESIALIS KANDUNGAN BATRA PEKANBARU - R. MUHAMMAD ZIKRI PRANOTO; NURFADLY . (LP2MTBM MAKARIOZ, 2021)
Toxoplasmosis is an infection caused by Toxoplasma gondii. Complications From toxoplasmosis in pregnant women can bein miscarriage of the baby who will be born. Knowledge is an aspect in preventing the risk of toxoplasmosis in pregnantwomen and is the duty of health services to increase knowledge and preventive attitudes of pregnant women. This studyaims to determine the level of knowledge and attitudes of pregnant women about toxoplasmosis at Batra obstetric specialistclinic Pekanbaru. This study is a descriptive analytic study with a cross-sectional study using a questionnaire as a researchinstrument. Sampling using Accidental Sampling amounted 107 pregnant women. Statistical analysis using thecrosstabulation method. The majority of pregnant women as housewives were 63.6%, aged 21-34 years were 82.2%, thelatest education was S1 / S2 / S3 ware 63.6%. and 100% positive attitude of pregnant women. The majority of pregnantwomen in the obstetrician clinic Batra Pekanbaru with a sufficient level of knowledge about toxoplasmosis and positiveattitudes of pregnant women about toxoplasmosis.